Modeling in Early Stages of Technology Development: Is an Iterative Approach Needed?; Comment on "Problems and Promises of Health Technologies: The Role of Early Health Economic Modeling" - Michael F. Drummond (Kerman University of Medical Sciences, 2020)
A recent paper by Grutters et al makes the case for early health economic modeling in the development of health technologies. A number of examples of the value of early modeling are given, with analyses being performed at different stages in the development of several non-drug health technologies. This commentary acknowledges the contribution of the paper by Grutters et al and argues for an iterative and integrated approach to early modeling, assessing the cost-effectiveness of the technology, the value of future research and the interaction with the manufacturer's pricing and revenue expectations.